Isoliquiritin Apioside Suppresses in vitro Invasiveness and Angiogenesis of Cancer Cells and Endothelial Cells - Kim, Aeyung; Ma, Jin Yeul (Frontiers in Pharmacology, 2018)
Several components isolated from Glycyrrhizae radix rhizome (GR), including glycyrrhizin, liquiritin, and liquiritigenin, have been shown to induce cancer cell death and inhibit cancer metastasis. Isoliquiritin apioside (ISLA), a component isolated from GR, has been effective for treating tetanic contraction and genotoxicity. However, the effects of ISLA on the metastasis and angiogenesis of malignant cancer cells and endothelial cells have not been reported. In this study, we found that up to 100 μM ISLA did not affect cell proliferation but efficiently suppressed the metastatic ability of HT1080 cells, as assessed by scratch-wound migration, Transwell® migration, scratch-wound invasion, Transwell® invasion, and three-dimensional spheroid invasion. ISLA significantly decreased phorbol 12-myristate 13-acetate (PMA)-induced increases in matrix metalloproteinase (MMP) activities and suppressed PMA-induced activation of mitogen-activated protein kinase as well as NF-κB, which are involved in cancer metastasis. In addition, ILSA treatment reduced the production of pro-angiogenic factors in HT1080 cells, including MMP-9, placental growth factor, and vascular endothelial growth factor under normoxia as well as hypoxia conditions, by impairing the hypoxia-inducible factor-1α pathway. We also found that the abilities of human umbilical vein endothelial cells to migrate across the Transwell® and to form tube-like structures were significantly reduced by ISLA treatment. Moreover, using the chorioallantoic membrane assay, vessel formation with or without vascular endothelial growth factor was significantly suppressed by ISLA. These results suggested that ISLA possesses anti-metastatic and anti-angiogenic abilities in malignant cancer cells and endothelial cells, with no cytotoxicity. ISLA may therefore be a safe and effective anti-cancer drug for limiting the spread of primary tumors to distant organs to form secondary tumors.